Basic principles and technologies for planted forests and nature-oriented forests in arid conditions - Manaenkov Alexander (BIO Web of Conferences)
Expanding the area of protective forests and forests in arid regions is an affordable and effective means of solving climate and food security in Russia. The purpose of this work is to systematize the achievements of science and practice in the field of forest land reclamation, aimed at increasing the effectiveness of work, productivity and functional durability of forest crops on sands and zonal soils of dry sub-humid and semi-arid regions. The main reason for the treelessness of arid plains, the concept of “forestability of land,” principles and criteria for its assessment, and patterns of geographic dynamics are discussed. Consistently presented afforestation methods, principles and techniques for creating and growing sustainable tree stands.